Intracranial Squamous Cell Carcinoma Arising From a Cerebellopontine Angle Epidermoid Cyst Remnant Four Decades After Partial Resection - Cuoco, Joshua A.; Rogers, Cara M.; Busch, Christopher M.; Apfel, Lisa S.; Entwistle, John J.; Marvin, Eric A. (Frontiers in Oncology, 2019)
Intracranial epidermoid cysts are benign lesions that typically remain asymptomatic; however, although histopathologically benign, these cysts can rarely undergo malignant transformation into squamous cell carcinoma. Primary intracranial squamous cell carcinoma carries a poor prognosis as optimal treatment modalities remain unclear due to their low incidence. Here, we present a case of a cerebellopontine angle epidermoid cyst remnant that underwent malignant transformation into squamous cell carcinoma 40 years after partial resection. To our knowledge, this case establishes the longest time interval to date for an intracranial epidermoid cyst to undergo malignant transformation. We also review the relevant literature and discuss recent retrospective clinical studies that have analyzed the effect of multimodal treatment approaches on survival outcomes in patients with these lesions.